National Geographic Magazine [computer file] 1940s (vol. LXXVII, no. 1) Jan. 1940-April 1943, May 1943-August 1946, September 1946-December 1949 (The Complete National Geographic Magazine : 110 years of National Geographic Magazine on CD-ROM, 1888)
See the high-speed photograpjs of dazzling hummingbirds, captured on a film at 1/3000 of a second. Explore the ruins of Colorado's Mes Verda cliff dwellings. Relive the liberation of Paris in 1944, with soldiers parading down streets still echoing with the lockstep march of Nazi Storm trooper boots. And experience manay more captivating moments from the 1940s.